Privatisierung und Vermarktlichung der Altersvorsorge: Eingetrübte Aussichten des deutschen Mehrsäulenmodells - Ebbinghaus, B (Nomos Verlagsgesellschaft, 2018)
Within seven decades, the German system of old-age security has undergone a paradigm shift from the Bismarckian model of pay-as-you-go pension insurance to the liberal multi-pillar model. Under the given fiscal constraints and facing future demographic ageing, the aim of guaranteeing living standards in old age has been shifted from state to private pillars. The voluntary -pre-funded “Riester” pension cannot sufficiently close the future pension gap. In addition, the recent financial market crisis has also shown the limits of funded pensions and occupational pensions require further expansion by the social partners to withstand challenges. The pension reforms thus far have been insufficient to protect against the increasing poverty risks among older people in a more flexibilised working society. A better minimum income protection within the pension insurance scheme and a broader coverage of supplementary pensions is needed to achieve both social and political sustainability in the future.